Effects of dexmedetomidine on cognitive function in elderly patients after laparoscopic cholecystectomy: A protocol for systematic review and meta-analysis. Issue 20 (15th May 2020) - Li, Na; Xiong, Lu; Wu, Ye-Hua; Chen, Xiao-Jian; Meng, Ya-Zhen; Li, Shuang-Feng; Xiong, Ya-Qin
Abstract: Background: Although many studies have reported the effects of dexmedetomidine on cognitive function (CF) in elderly patients after laparoscopic cholecystectomy (LCT), to this date, its effects are still not well understood. The aim of this study is to produce a qualitative synthesis of assessing the effects of dexmedetomidine on CF in elderly patients after LCT. Methods: We will conduct a comprehensive search in Cochrane Library, MEDLINE, EMBASE, CINAHL, PsycINFO, Scopus, VIP Database, WANGFANG Database, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure from the commencement to March 31, 2020 without restrictions of language and publication status. In addition, we will also search grey literature, including conference abstracts, dissertations, reference lists of included studies and relevant reviews. All potential studies will be identified independently by 2 authors to determine their inclusion against previously defined eligibility criteria. The quality of selected papers will be assessed using Cochrane risk of bias tool. All statistical analysis will be performed using RevMan 5.3 software. Results: This study will provide a synthesis of the current available data on assessing the effects of dexmedetomidine on CF in elderly patients after LCT. Conclusions: Its findings will provide qualitative evidence to better understand the effects of dexmedetomidine on CF in elderly patients after LCT. INPLASY Registration Number: INPLASY202040030.